Longitudinal changes of amplitude of low-frequency fluctuations in MDD patients: A 6-month follow-up resting-state functional magnetic resonance imaging study - Wang, Mi; Ju, Yumeng; Lu, Xiaowen; Sun, Jinrong; Dong, Qiangli; Liu, Jin; Zhang, Liang; Zhang, Yan; Zhang, Shuai; Wang, Zengguang; Liu, Bangshan; Li, Lingjiang (Journal of affective disorders, 2020)
•Decreased ALFF of the right PCUN/PCC in MDD patients compared with HCs, which persists to clinical remission after 6-month.•ALFF in the right PCUN/PCC was not correlated with severity, illness duration, onset age and number of episodes in acute MDD.•There is no correlation between changes of ALFF value and depression improvement in remitted MDD subgroup. The aim of this study includes: (1) using resting-state functional magnetic resonance imaging (rsfMRI) to explore the aberrant brain regional spontaneous brain activities in acute major depressive disorder (MDD) patients; (2) to determine whether the abnormalities could be restored after 6 months of antidepressant treatment; (3) to investigate whether the differences in regional spontaneous brain activities are associated with clinical variables in MDD. RsfMRI scanning was performed in 149 MDD patients and 122 healthy control (HC) subjects at baseline. After 6 months of antidepressant treatment, rsfMRI scanning was reperformed in remitted MDD patients (MDD-R) (n=63). The characteristics of the amplitude of low-frequency fluctuations (ALFF), and the relationship between the fMRI representatives and clinical variables in the MDD group were analyzed. (1) Compared to healthy controls, significantly decreased ALFF in the right precuneus/posterior cingulate cortex (PCUN/PCC) was detected in MDD. (2) The ALFF value of precuneus in MDD-R group did not change significantly after a 6-month antidepressant treatment and was still lower than the HC group when remission was achieved (P = 0.002). (3) No correlations were found between ALFF in the right PCUN/PCC and Hamilton Depression Rating Scale(HAMD) total score, illness duration, age of onset, and the number of episodes in the baseline MDD group. The ALFF change was not correlated with depressive symptom improvement in MDD-R group. The reduction of ALFF in the precuneus persisted in MDD who achieved clinical remission, suggesting that the decreased ALFF in PCUN/PCC may be a trait marker of MDD.